(untitled) (Pedagogy of Higher and Secondary Education, 2014)
Lytvynenko I. Yu. The role of integration in English reading teaching of the students of technical specialties. The article represents the methods of English reading teaching of the students of technical specialities, particularly at the level of reading through integrative methods. The article discusses the features of a speech competence and international requirements of its levels, and some methodical ways of improving English reading. This English competence will help a technical specialist in his future professional activity.